2008
DOI: 10.1007/s00432-008-0509-9
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor mutations in non-small cell lung cancer influence downstream Akt, MAPK and Stat3 signaling

Abstract: We show that the phosphorylation of tyrosine residues 922 and 1173, but not 1068, are primarily affected by the activating EGFR mutations. Akt activity was significantly higher in patients with EGFR mutations but we found no difference in Stat3 or MAPK phosphorylation. Our results suggest that EGFR mutations not only increase receptor activity, but also alter responses of downstream signaling cascades in human NSCLCs and that these finding differ from results obtained in cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 28 publications
4
33
0
1
Order By: Relevance
“…There was no significant difference in pSTAT3 expression between the EGFR-mutated (83%) and EGFR-wild-type tumors (56%), and the expression of pSTAT3 was not a result of EGFR kinase activity in NSCLC [25]. pSTAT3 was generally observed irrespective of the EGFR mutation status in the present study, confirming previously published data [25].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There was no significant difference in pSTAT3 expression between the EGFR-mutated (83%) and EGFR-wild-type tumors (56%), and the expression of pSTAT3 was not a result of EGFR kinase activity in NSCLC [25]. pSTAT3 was generally observed irrespective of the EGFR mutation status in the present study, confirming previously published data [25].…”
Section: Discussionsupporting
confidence: 93%
“…pSTAT3 was generally observed irrespective of the EGFR mutation status in the present study, confirming previously published data [25]. Although their analysis included squamous cell carcinoma at a more advanced stage, the researchers suggested that STAT3 activity contributes to the carcinogenic potential of NSCLC independent of EGFR mutations.…”
Section: Discussionsupporting
confidence: 92%
“…For example, the phosphorylation of Y1068 can recruit GAB-1 or growth factor receptor-bound protein 2 (Grb-2) to activate survival signals (40), whereas the phosphorylation of Y1173 is responsible for eliciting the activation of ERK via inhibition of the SH2 domain-containing transforming protein (SHC) and Grb2 (41,42). Furthermore, the up-regulation of pY1173 also has been reported in patients who have NSCLC with EGFR mutation, and Akt, MAPK, and Stat3 signaling is higher in pY1173-positive patients (43). It also has been shown that patients with stage IIIb and IV NSCLC with positive pY1173 staining have a shorter superior progression-free survival rate than patients with negative pY1173 staining (44).…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 may be one of the key oncogenic drivers in NSCLC. [6][7][8][9][10][11][12][13][14] However, several studies have found that STAT3 also plays a role in tumor suppression, [15][16][17][18][19] which should be taken into consideration in cancer therapies based on STAT3 inhibition. In this review, we focus on the molecular function of STAT3.…”
Section: Introductionmentioning
confidence: 99%